STUDY THE EFFECTS OF SPEEDS AND DEPTHS OF PLOWING ON SOME TECHNICAL INDICATORS USING ROTARY PLOW PERFORMANCE TYPE MINI 1200 - Abdulrahman, Riyad Abdulhamd (Diyala Agricultural Sciences Journal, 2017)
An experiment carried out at the field of College of Agricultural, University of Diyala during the autumn season 2015 - 2016. To study the effect of speed and depth of plowing on rotary plow performance. By using the machine unit consists of orchard tractor type B 2530 and mini rotary plow type 1200 in clay Loam soil. The experiment was done by using random complete block design (RCBD) as a full factorial experiment with two factors. The first factor represents the plowing depths with two levels 2-4 cm and 8-10 cm, while the second factor represents the forward speed of tractor with three levels 1.66, 3.05 and 4.35 km h-1 with three replicates. The results showed that: the depth 2-4 cm shows higher significantly affected than depth 8-10 cm of all study parameters except the volume of soil distribution character with less slippage percentage. And the results also showed that the speed 4.35 km h-1 has highly affected comparing with speeds 3.05 and 1.66 km h-1 on all study parameters under lower slippage percentage too. Meanwhile the interaction between the first speeds 1.66 km h-1 with the first depth 2-4 cm showed higher significantly affected than other interactions for speed using coefficient and actual field capacity parameters with less slippage percentage. And obtain the highest production on third speed 4.35 km h-1 with 2-4 cm depth 0.401 hectare h-1 and the third speed with depth 8-10 cm showed highest volume of the soil distribution under 0.05 probability levels. Concluding from this: that the increasing the speed of the tractor has led to increasing of effective field capacity, the volume of soil distribution, field efficiency and the coefficient of speed exploit at the lowest of slippage percentage. While the increasing in the depth of tillage led to increasing of the slippage percentage and the volume of soil distribution with a decreasing in coefficient of speed exploit, field efficiency and effective field capacity coefficient. Thus the recommendation of plowing process by using the rotary plow at the shallow depths with high speeds to obtain the highest values of the characteristics studied